2017
DOI: 10.1136/bmjresp-2017-000202
|View full text |Cite
|
Sign up to set email alerts
|

Breathing–swallowing discoordination is associated with frequent exacerbations of COPD

Abstract: IntroductionImpaired coordination between breathing and swallowing (breathing–swallowing discoordination) may be a significant risk factor for the exacerbation of chronic obstructive pulmonary disease (COPD). We examined breathing–swallowing discoordination in patients with COPD using a non-invasive and quantitative technique and determined its association with COPD exacerbation.MethodsWe recruited 65 stable outpatients with COPD who were enrolled in our prospective observational cohort study and did not manif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 32 publications
1
42
3
5
Order By: Relevance
“…Our results differed from the previous reports, which stated that the SSPT results correlated with the history of COPD exacerbation . Patients with COPD are reported to present a characteristic change in the coordination of deglutition and respiration, which may contribute to their dysphagia . This unique pathophysiology of dysphagia may be the reason why dysphagia in patients with COPD is more pronounced in repetitive efforts such as the RSST, instead of a one‐time‐only reflection test such as the SSPT.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results differed from the previous reports, which stated that the SSPT results correlated with the history of COPD exacerbation . Patients with COPD are reported to present a characteristic change in the coordination of deglutition and respiration, which may contribute to their dysphagia . This unique pathophysiology of dysphagia may be the reason why dysphagia in patients with COPD is more pronounced in repetitive efforts such as the RSST, instead of a one‐time‐only reflection test such as the SSPT.…”
Section: Discussioncontrasting
confidence: 99%
“…3,4 Patients with COPD are reported to present a characteristic change in the coordination of deglutition and respiration, which may contribute to their dysphagia. 11 This unique pathophysiology of dysphagia may be the reason why dysphagia in patients with COPD is more pronounced in repetitive efforts such as the RSST, instead of a one-time-only reflection test such as the SSPT. The poor concordance between the results of SSPT and other screening tests (Table 5) also indicates the possibility that SSPT is not useful in the otherwise healthy COPD population.…”
Section: Discussionmentioning
confidence: 99%
“…The Bell's disease classification guidelines include the ability to reliably predict adverse clinical outcomes and patient responses to potential therapies . In this context, the KCL can extract detailed problems in various domains, such as activities of daily living, locomotor function, oral function, cognitive function and mental burdens, which tend to be underdiagnosed despite their importance in patients with COPD . Therefore, this model can be used to enable rapid and effective interventions for patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an increase in I-SW pattern is associated with a risk of aspiration in Parkinson's disease (Troche et al, 2011 ). Recently, we reported that frequent I-SW and/or SW-I patterns (high I-SW/SW-I rate) exacerbated COPD (Nagami et al, 2017 ). Therefore, the identification of such subjects with a high I-SW/SW-I rate and treating them to reduce the I-SW/SW-I rate may prevent exacerbations of these diseases.…”
Section: Introductionmentioning
confidence: 99%